2005
DOI: 10.1017/s0265021503001339
|View full text |Cite
|
Sign up to set email alerts
|

Levobupivacaine 0.25% compared with ropivacaine 0.25% by the caudal route in children

Abstract: We conclude that levobupivacaine 0.25% 1 mL kg(-1) provides caudal block of comparable onset and duration, as produced by the same volume and concentration of ropivacaine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 14 publications
2
17
0
2
Order By: Relevance
“…Previous studies have indicated that caudal block with high volume ⁄ low concentration is more effective than low volume ⁄ high concentration of local anaesthetic in blocking spermatic cord traction response during orchidopexy [12]. In general, the concentration of levobupivacaine used in paediatric caudal block is commonly 0.25% [5,[13][14][15]. Based on our current results, 0.15% levobupivacaine might represent a more suitable concentration for caudal blockade in children.…”
Section: Discussionsupporting
confidence: 49%
“…Previous studies have indicated that caudal block with high volume ⁄ low concentration is more effective than low volume ⁄ high concentration of local anaesthetic in blocking spermatic cord traction response during orchidopexy [12]. In general, the concentration of levobupivacaine used in paediatric caudal block is commonly 0.25% [5,[13][14][15]. Based on our current results, 0.15% levobupivacaine might represent a more suitable concentration for caudal blockade in children.…”
Section: Discussionsupporting
confidence: 49%
“…However, other studies [1,17] indicated that caudal blocks with high volume/low concentration of LA, or vice versa, were more effective in blocking spermatic cord traction response during orchidopexy, but the investigated dose in both cases (2 mg • kg -1 ) was higher than the dose administered in our first group (1.5 mg • kg -1 ). Because pediatric patients were involved in this study, the doses of LA used were reduced and thereby toxicity of LA was avoided similar to other studies [7,[18][19][20] that did not report adverse events of LA when the recommended dose of 2.5 mg • kg -1 was used. However, adequate care should be taken regarding pediatric patients as recommended previously [21,22] .…”
Section: Discussionmentioning
confidence: 99%
“…So far, very few studies have been published comparing ropivacaine and levobupivacaine for regional anesthesia in children. [101112]…”
Section: Discussionmentioning
confidence: 99%